2020
DOI: 10.1093/jac/dkaa110
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled tigecycline is effective against Mycobacterium abscessus in vitro and in vivo

Abstract: Background Mycobacterium abscessus causes chronic pulmonary infections. Owing to its resistance to most classes of antibiotics, treatment is complex and cure rates are only 45%. Tigecycline is active against M. abscessus, but severe toxicity and the need for IV administration limit its use. Objectives To assess the potential of inhaled tigecycline as a treatment for M. abscessus pulmonary disease, by measuring its efficacy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Similarly, a small case series of paediatric patients with CF and M. abscessus demonstrated potential clinical utility of inhaled imipenem/cilastatin [136]. In a recent study in a mouse model of M. abscessus, inhaled tigecycline was highly efficacious and demonstrated intracellular activity within macrophages, an important finding given the limitations posed by intravenous tigecycline toxicity [137]. These studies, along with established data of lung penetration of inhaled non-liposomal amikacin, support the rationale that inhaled drug delivery can provide targeted delivery with the potential to limit systemic exposure.…”
Section: Challengesmentioning
confidence: 95%
“…Similarly, a small case series of paediatric patients with CF and M. abscessus demonstrated potential clinical utility of inhaled imipenem/cilastatin [136]. In a recent study in a mouse model of M. abscessus, inhaled tigecycline was highly efficacious and demonstrated intracellular activity within macrophages, an important finding given the limitations posed by intravenous tigecycline toxicity [137]. These studies, along with established data of lung penetration of inhaled non-liposomal amikacin, support the rationale that inhaled drug delivery can provide targeted delivery with the potential to limit systemic exposure.…”
Section: Challengesmentioning
confidence: 95%
“…The acquisition of resistance mechanisms is in some cases facilitated by the horizontal transfer of broad‐host range plasmids from other Gram‐positive of Gram‐negative with which M. abscessus shares the same environmental and host habitats 31 . Despite these limitations, a number of drug candidates targeting DNA, RNA and protein synthesis, including oxazolidinones (e.g., tedizolid; delpazolid), rifamycins, 32 tetracyclines (e.g., tigecycline, omadacycline, eravacycline, TP‐271), 33‐35 fluoroquinolones (DC‐159a), 36 and other DNA gyrase‐ and topoisomerase type IA‐targeting agents (e.g., SPR719/SPR‐720; bis(pyrrolide‐imine) gold(III) macrocycles and chelates) 37,38 are currently at different stages of preclinical and clinical development for their increased potency over first‐generation antibiotics, reduced toxicity, oral bioavailability, or enhanced ability to synergize with other antibiotics (see further sections). Concurrently, other studies are assessing novel inhaled liposomal formulations of standard‐of‐care antibiotics in an effort to increase concentrations at the site of infection while limiting systemic toxicity.…”
Section: Drug Targets In M Abscessus For Present and Future Therapeutic Applicationsmentioning
confidence: 99%
“…Accordingly, liposomal formulations of amikacin for inhalation, alone and in combination regimens, have undergone clinical trials in patients with M. avium and M. abscessus pulmonary infections (http://ClinicalTrials.gov: NCT01315236, NCT02344004, NCT03038178). Inhaled tigecycline has proven highly effective against M. abscessus in macrophages and in mice 35 . Liposomal formulations of ciprofloxacin also proved effective in animal models of M. abscessus and M. avium infection but have so far only been the object of clinical trials for chronic infections caused by Pseudomonas aeruginosa 39 .…”
Section: Drug Targets In M Abscessus For Present and Future Therapeutic Applicationsmentioning
confidence: 99%
“…In vitro evidence suggests tedizolid has concentration-dependent activity against M. avium, and results from a case report demonstrated that tedizolid was used as an alternative treatment in a patient who was diagnosed with NTM-LD caused by MAC and M. kansasii and experienced intolerance to linezolid [128,129]. Other treatment modalities that are being investigated in NTM-LD, with very limited data specifically in MAC-LD, include non-antibiotic interventions such as immunomodulation, hypertonic saline inhalation and other airwayclearance methods, omadacycline, inhaled tigecycline, and mycobacteriophages [130][131][132][133][134][135].…”
Section: Investigational Approaches In Mac-ldmentioning
confidence: 99%